Optimization of Drive Parameters for Resolution, Sensitivity and Safety in Magnetic Particle Imaging - Tay, Zhi Wei (IEEE Trans Med Imaging, 2019)
Magnetic Particle Imaging is an emerging tracer imaging modality with zero background signal and zero ionizing radiation, high contrast and high sensitivity with quantitative images. While there is recent work showing that the low amplitude or low frequency drive parameters can improve MPI’s spatial resolution by mitigating relaxation losses, the concomitant decrease of the MPI’s tracer sensitivity due to the lower drive slew rates was not fully addressed. There has yet to be a wide parameter space, multi-objective optimization of MPI drive parameters for high resolution, high sensitivity and safety. In a large-scale study, we experimentally test 5 different nanoparticles ranging from multi to single-core across 18.5 nm to 32.1 nm core sizes and across an expansive drive parameter range of 0.4 – 416 kHz and 0.5 – 40 mT/μ(0) to assess spatial resolution, SNR, and safety. In addition, we analyze how drive-parameter-dependent shifts in harmonic signal energy away and towards the discarded first harmonic affect effective SNR in this optimization study. The results show that when optimizing for all four factors of resolution, SNR, discarded-harmonic-energy and safety, the overall trends are no longer monotonic and clear optimal points emerge. We present drive parameters different from conventional preclinical MPI showing ~ 2-fold improvement in spatial resolution while remaining within safety limits and addressing sensitivity by minimizing the typical SNR loss involved. Finally, validation of the optimization results with 2D images of phantoms was performed.